Shale gas characterization of the Dinder and Blue Nile Formations in the Blue Nile Basin, East Sudan - Monera Adam Shoieb, Chow Weng Sum, Swapan Kumar Bhattachary, Nor, . (2016)
The development of gas and oil in unconventional plays in United State and Northern Europe has affected the finances and the energy security. Geochanical properties of shale rocks can have a major impact on the efficiency of shale gas exploration. The goal of this study is to evaluate shale gas potentiality in the Blue Nile Basin, using samples from existing drilled wells.